Value for money (VFM) in private finance initiative (PFI) implementation in Malaysia - Ahmad @ Abdul Mutalib, Hawa; Ismail, Suhaiza; Zakaria, Zamzulaila (Emerald Publishing Limited, 2023)
Purpose Drawing on institutional work (Lawrence and Suddaby, 2006; Lawrence et al., 2011), this study aims to explore how the concept of value for money (VFM) is understood in terms of the private finance initiative (PFI) implementation in Malaysia.